Quantitative Skills, Critical Thinking, and Writing Mechanics in Blended Versus Face-to-Face Versions of a Research Methods and Statistics Course. (April 2018) - Goode, Christopher T.; Lamoreaux, Marika; Atchison, Kristin J.; Jeffress, Elizabeth C.; Lynch, Heather L.; Sheehan, Elizabeth
Hybrid or blended learning (BL) has been shown to be equivalent to or better than face-to-face (FTF) instruction in a broad variety of contexts. We randomly assigned students to either 50/50 BL or 100% FTF versions of a research methods and statistics in psychology course. Students who took the BL version of the course scored significantly lower on measures of quantitative mastery of statistical concepts than those who took the FTF version; however, the size of this effect was quite small. We detected no significant difference between BL and FTF in the expression of critical thinking through writing or writing mechanics. The greatest difference in performance was among instructors regardless of instruction type. We discuss these results in the context of increasing online and BL instruction, particularly with regard to teaching psychological statistics, research methods, and critical thinking.